2009
DOI: 10.1007/s10551-009-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Strategic Rationality: Ethics, Enterprise Risk Management, and Governance

Abstract: decision-making, enterprise risk management, ethics, strategic management,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 7 publications
(5 reference statements)
0
21
0
1
Order By: Relevance
“…Anything that could affect the organizational reputation, the image or the brand is a potential source of reputational risk [9,10], but its management is frequently insufficient or inexistent in numerous organizations [36]. In fact, inadequate management of any risk can lead to reputational damage [37], because reputational risk shows how wide, important and imprecise the risks that may affect an organization can be [38]. This reputational damage can manifest in several different ways.…”
Section: Reputation As a Risk Sourcementioning
confidence: 99%
“…Anything that could affect the organizational reputation, the image or the brand is a potential source of reputational risk [9,10], but its management is frequently insufficient or inexistent in numerous organizations [36]. In fact, inadequate management of any risk can lead to reputational damage [37], because reputational risk shows how wide, important and imprecise the risks that may affect an organization can be [38]. This reputational damage can manifest in several different ways.…”
Section: Reputation As a Risk Sourcementioning
confidence: 99%
“…Avram and Kahne (2008) argued that firms could charge a premium for their CSR-oriented approaches. The sustainable products" market positioning could be improved through the use of social responsibility and responsible supply chain management (Palazzo and Basu, 2007), There are positive implications for certain firms that pursue differentiation strategies (through social and environmentally responsible practices) as a means to signal an image of high product quality and sustainability to consumers (Tate et al, 2010), As a matter of fact, numerous findings reported how socially responsible business practices are actually improving both brand equity and organisational performance (Lai, Chiu, Yang, and Pai, 2010;Castaldo, Perrini, Misani and Tencati, 2009), On the other hand, some other contributions have indicated that there is little evidence on socially responsible firms that pursue niche strategies in narrow markets (Van De Ven and Jeurissen, 2005;Weitzner and Darroch, 2010), It may appear that the supply chain literature has often ignored how niche firms develop their supply chain strategies (Baier et al, 2008;13 Cousins, 2005), Perhaps, it may prove difficult for academia to propose a specific relationship between niche strategy and socially responsible supply chain management. The responsible procurement of materials and products may not necessarily constitute a part of the firms" strategy.…”
Section: The Link Between Responsible Supply Chain Management and A Dmentioning
confidence: 99%
“…The responsible procurement of materials and products may not necessarily constitute a part of the firms" strategy. Notwithstanding, the promotion of the responsible supply chain management could be beneficial if it is directed toward socially conscious consumer groups (Weitzner andDarroch, 2010), Weitzner and Darroch (2010) argued that there is a wide array of niche strategies that strive in their endeavours to appeal to different market subgroups. The specialised products that are marketed using a niche strategy will be easily distinguishable from other competitors" products.…”
Section: The Link Between Responsible Supply Chain Management and A Dmentioning
confidence: 99%
“…The tension between strategy and ethics or the dichotomy between the used criteria, priorities, and values are raised by several authors (Behnam and Rasche, 2009;Singer, 2009;Weitzner and Darroch, 2010). For Elms, Brammer, Harris, and Philips (2010) "the two fields started with similar interests, diverged, and are beginning to converge again" (p.401), whereas Singer (2009) states that "strategy and ethics have long been regarded as expressions of contrasting valuepriorities" (p.480).…”
Section: Introductionmentioning
confidence: 99%